EFFECT OF TANGIBILITY AND RELIABILITY SERVICE QUALITY TOWARDS HOMESTAY CUSTOMER SATISFACTION - Sharifah Norhuda Syed Wahid; Mohamad Ridhuan Mat Dangi; Faizan Abd Jabar; Mohd Faizal Azrul Azwan Muhamed; Halil Paino (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
A homestay programme gives local and international tourists an opportunity to stay with a chosen family, interact and experience their daily life. They can also learn the culture and lifestyle of the rural communities in Malaysia. This programme is much related to the service quality provided by the homestay operators including tangible and reliable dimensions. Therefore, the purpose of this study is to determine the effect of these two dimensions on customer satisfaction. In total, 102 customers were selected and they stated that on the average, the tangible quality was rated as 4.95 out of 10 points which indicated that the overall tangible quality provided did not meet the customers’ needs. Meanwhile, the reliability quality was rated higher than tangible quality (M = 6.95). The regression analysis revealed that the tangible and reliability has significant direct effect towards customer satisfaction (β1 = .676, p = .000; β2 = .466, p = .000). Furthermore, 58.30% of customer satisfaction was influenced by tangible and reliability quality itself. The study is hoped to provide a direction for service quality improvement especially in tangible and reliability of service quality dimensions to the homestay programme, and also the service industry in general. In addition, the findings could also be used for future research in the subjects of other service quality dimensions.